DEVELOPMENT OF A DUAL PURPOSE REFRIGERATION SYSTEM FOR DOMESTIC USE (Nigerian Journal of Technology, 2016)
Refrigeration and air conditioning are very important in the daily activities of man, particularly in the tropical regions of the world; used in the preservation of perishable items, storage of pharmaceutical drugs, controlling of an atmospheric environment either for human/animal thermal comfort or effective performance of a scientific process. This paper is aimed at the design and construction of a dual purpose domestic refrigeration system, that can simultaneously function as a refrigerator and as well as an air conditioner henceforth known as REFACON. The refrigeration system employed was a vapour compression system. The machine was a split configuration with an Indoor and an outdoor unit (condensing unit). The machine used a singular 1,119 W single phase hermetically sealed reciprocating compressor, a fabricated condenser and split evaporator operated by temperature controlled solenoid valve. The system used 0.620 kg of R 22 refrigerant, with a discharge pressure of 1,355 kPa and suction pressure of 360 kPa. The input power was 1,350 W with an output cooling effect of 5,280 W. The combined cooling load/cooling capacity of the machine was 4,500 W. The results of tests conducted showed a total heat rejected of 6,680 W and a total evaporator heat absorption of 5,179 W. The Energy Efficiency Ratio was 3.91 while the Coefficient of Performance was 4.72. This research has shown that the design employed for the heat exchangers was appropriate and Thermal contact resistance cannot be neglected. http://dx.doi.org/10.4314/njt.v35i4.16